The Effect Of Capital And Licensing On The Productivity Of Umkm In Majalengka Regency - Khoirul Umam, Muhammad; Abdurokhim, Abdurokhim (Winter Journal: IMWI Student Research Journal, 2024)
his research aims to determine the effect of Capital and Licensing on the Productivity of MSMEs in Majalengka Regency. The study was conducted on MSMEs in the Majalengka Regency with a sample size of 100 respondents. Using the Simple Random Sampling technique, the respondents were selected to obtain a representative sample from 211,749 MSMEs in the Majalengka Regency. The data analysis method used validity tests, reliability tests, classical assumptions, regression analysis, and T-tests and F-tests processed through IBM SPSS 26. The research results indicate that partially there is a significant positive effect of the Capital and Licensing variables on the Productivity of MSMEs. At the same time, simultaneously there is a significant positive effect of 77.2%, with other factors not examined in this study contributing 22.8%. To that end, MSMEs must strive to improve access to capital by preparing attractive business proposals, and they also need to ensure that all necessary permits have been properly arranged. Furthermore, support from the government is crucial in reducing the bureaucratic burdens faced by MSMEs, simplifying the requirements for KUR, and lowering interest rates